2005
DOI: 10.2320/matertrans.46.858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tantalum on Corrosion Resistance of Ni–Nb(–Ta)–Ti–Zr Glassy Alloys at High Temperature

Abstract: Ni 60 Nb 20Àx Ta x Ti 15 Zr 5 (x ¼ 0, 5, 15 and 20 at%) glassy alloys with high thermal stability and high corrosion resistance have been synthesized by the melt spinning technique. The substitution of tantalum for a portion of niobium in the Ni 60 Nb 20 Ti 15 Zr 5 glassy alloy causes a significant increase in the supercooled liquid region (ÁT x ¼ T x À T g ) from 52 K at 0 at% Ta to 67 K at 20 at% Ta accompanied by an increase in T g and T x . The glassy alloys are spontaneously passivated in a wide passive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is noticed that these alloys contain high Cu content, leading to decreases of the corrosion resistance in aggressive media, especially in the chloride-ioncontaining solutions, 7,8) which limit their practical application in the PEMFC 9) and other Chloride-ion-related environment. In addition, the Cu-containing BMGs exhibit low plasticity in spite of their high fracture strength.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that these alloys contain high Cu content, leading to decreases of the corrosion resistance in aggressive media, especially in the chloride-ioncontaining solutions, 7,8) which limit their practical application in the PEMFC 9) and other Chloride-ion-related environment. In addition, the Cu-containing BMGs exhibit low plasticity in spite of their high fracture strength.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have investigated the effect of different elements on the corrosion resistance of the Ni-Nbbased glassy alloys, and found that substitution of Ta for Nb in the Ni-Nb-based glassy alloys was very effective for increasing the corrosion resistance in fluoride containing acid solution at a high temperature. 27) However, little is known about the effect of substitution of Ta for Nb on the thermal stability of the supercooled liquid, glass-forming ability and mechanical properties of the Ni-Ta-based glassy alloys. The heats of mixing in the Ni-Nb and Ni-Ta pairs as well as the atomic sizes of Ta and Nb are similar with each other.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, quaternary Nb-Ni-Ti-Zr glassy alloys have been reported to exhibit high hydrogen impermeability, corrosion resistance, and formability when used as bipolar plates in fuel cells. 4,5) Although the glassy-or amorphous-forming (hereafter referred to as ''glass-forming'') composition ranges of these ternary and quaternary alloys have been investigated experimentally, 1,2,6) information on their glass-forming ability, as well as the phase diagram, especially phase equilibria involving the liquid phase, would be useful for understanding their thermal stability and for further development of these hydrogen energy-related materials. In our previous work, 7) a thermodynamic study of the phase equilibria in the Nb-Ni-Ti-Zr quaternary system was carried out using the Calculation of Phase Diagrams (CALPHAD) method.…”
Section: Introductionmentioning
confidence: 99%